Intergenerational correlations in labor market status: A comparison of the United States and Germany - Kenneth A. Couch; Thomas A. Dunn (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper uses data from the Panel Study of Income Dynamics, and the German Socioeconomic Panel to calculate comparable measures of the intergenerational correlations of earnings, hours, and education in the United States and Germany. Our results indicate that there is remarkable similarity across the two countries in the correlations of earnings and of annual work hours of fathers and sons. All of the correlations which involve women appear to weaker in Germany than the United States, perhaps due to the greater integration of women in the United States into the labor market. We find weak correlations in earnings and work hours for parent-child pairs of different sexes in both countries. We also find intergenerational correlations in educational attainment are considerably stronger in the U.S.
Keywords: 330